Multiple sclerosis: II. Effects of prothymosin alpha on the autologous and allogeneic MLR in patients with multiple sclerosis. - Reclos, G J (1987)
We have recently demonstrated that peripheral blood monocytes from patients with multiple sclerosis (MS) have a defect in stimulating autologous and allogeneic T lymphocytes. This defect was found to correlate with disease activity. In this report we demonstrate that prothymosin alpha (ProT alpha), a rat thymus fraction 5 polypeptide, restores the MS monocyte stimulatory defect. The concentrations of ProT alpha which induced optimal enhancement of the mixed lymphocyte responses (MLR) were significantly higher when monocytes from patients with active disease were used as stimulators than when monocytes from patients with inactive disease were used. T4+ cells tested with autologous stimulatory monocytes harvested from an inactive stage of MS exhibited considerably higher proliferative responses than when stimulated with autologous monocytes obtained from an acute relapse. The decreased autologous proliferation of T4+ cells in MS patients was restored to normal levels after preincubation with ProT alpha in the environment of autologous monocytes. Our results demonstrate that ProT alpha is capable of fully restoring the deficient stimulatory function of MS monocytes and monocyte-associated functional defects of MS-derived T4+ cells.